Bacteriophage-based control of biogenic hydrogen sulphide produced by multidrug resistant Salmonella enterica in synthetic sewage. Issue 4 (August 2021) - Salim, Amrita; Madhavan, Ajith; Babu, Pradeesh; Porayath, Chandni; Kesavan, Manjumol; Hely, Sreetha; Kumar, V. Anil; Nair, Bipin G.; Pal, Sanjay
Abstract: Sulphate-reducing bacteria (SRB) is widespread in sewers and wastewater treatment plants. They generate hydrogen sulphide (H2 S) through anaerobic respiration using sulphur compounds as a terminal electron acceptor. H2 S apart from causing undesired odour, is also responsible for corrosion in sewerage systems. Approaches in controlling odour and corrosion essentially involve the prevention of sulphide generation by SRBs. With that objective, bacteriophages were investigated for their potential in reducing H2 S, using a multidrug resistant (MDR) Salmonella enterica clinical strain as a model SRB in simulated synthetic sewage settings. Two lytic phages specific to S. enterica were isolated from wastewater collected from the effluent treatment plant. The phages ϕPh_Se01 and ϕPh_Se02 possessed different plaque morphology and exhibited a distinct host range. Burst sizes of ϕPh_Se01 and ϕPh_Se02 were estimated to be 42 and 27 phages per infected cell respectively, with a latent period of 10 ± 5 min. Furthermore, nucleic acid analysis and melt curve profiles confirmed the diversity of these phages. Additionally, quantitative characterisation with regards to their stability in 10% (v/v) chloroform was used to comprehend their tolerance in large scale production. The study successfully demonstrated the application of ϕPh_Se01 and ϕPh_Se02 in the reduction of H2 S by 62% and 70% respectively, within 6 h in synthetic sewage compared with the non-phage control. We also investigated the bacteriolytic ability of ϕPh_Se01 and ϕPh_Se02 in reducing the S. enterica by 4-log. This study demonstrates the potential of phage-mediated reduction of H2 S and infection in wastewater. Graphical Abstract: ga1 Highlights: Bacteriophage-based control of biogenic H2 S and infection in wastewater. Over 70% reduction in biogenic H2 S within 6 h treatment. 4-log reduction of Salmonella enterica population in 6 h. Prospective applications in reduction of metal corrosion & odour caused by H2 S.